Student Religious Literacy: A Study of Student Religious Book Preferences State Universities in Indonesia - Nurhattati; Retno Kartini; Jerry Hendrayana; Ahmad Jauhari H.Ripki; Rihlah Nur Aulia; Choirul Fuad Yusuf (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2023)
This study aims to describe and analyze: (1) preference for reading religious books; (2) religious literacy, factors that influence the preference for reading religious books, and (3) formulate recommendations for the development of religious books in State Public Universities. This research used the survey method and literature review. The population is students of State Public Universities in Java, who are Muslims, including: DKI Jakarta, Banten, West Java, Central Java, Yogyakarta Special Region, and East Java. Each province has two State Public Universities, except for Banten, with a sample of 560 respondents, with a distribution of 53-60 respondents. Data collection techniques using literature review. The results of the study: First, the preference for reading religious books is at a „medium“ level, due to a number of factors including: (1) time-consuming college assignments, (2) low motivation due to perceptions of religious issues as „personal rights“, (3) an Islamic Religious Education environment that is less „motivating“, „reinforcing“, (4) the availability of religious books is not suitable for students' needs, and (5) the academic climate is less conducive which limits freedom, the breadth of reading religious books. Second, religious literacy, the micro dimension, is in a moderate position, namely the preference for reading religious books „sufficiently“has a significant effect on the development of students' abilities. Research contributions: (1) provide a factual map of preference for religious/religious books in the millennial generation at public universities in the 2018-2022 range. (2) drafting policy, providing religious books for public higher education.